A NEW FACILE METHOD FOR SPIN-LABELING OF OLIGONUCLEOTIDES - Strube, Thorsten; Schiemann, Olav; MacMillan, Fraser; Prisner, Thomas; Engels, Joachim W. (Nucleosides, nucleotides & nucleic acids, 2001)
A new facile method for spin-labeling suitable for DNA and RNA oligonucleotides is presented. The nitroxide 3-ethenyl-2,2,5,5-tetramethyl-pyrrolin-1-yloxy was directly introduced during automated solid-phase synthesis by a Pd(0) cross coupling reaction. The main advantages of this procedure are the small amount of spin-label needed for the derivatisation of the oligonucleotide and the high coupling efficiency on the solid phase.